(untitled) (Perner’s Contacts, 2009)
The paper deals with problems arising in a passenger railway station during realtime operation when delays of incoming trains can disturb the timetable and the platform allocation plan. In such a situation a dispatcher must operatively solve the problems related to possible conflicts of train movements. In the paper, a dispatcher’s decision-making process is formalised using a mathematical programming approach. Inputs to the model contain potential delays of incoming trains. Outputs from the model are decisions on: which platform track is to be assigned to the arriving train and how long connecting trains should wait for the incoming delayed train. The objective function combines multiple criteria which encompass two goals: to reduce disturbance propagation through the railway network, i.e. to minimise deviations from the timetable, and at the same time to minimise the inconvenience put to the passengers. The model can be used as a realtime decision support for a dispatcher or as a part of a relevant simulation model.